Motivational Interviewing in permanent supportive housing: The role of organizational culture - van den Berk-Clark, Carissa (Adm Policy Ment Health, 2015)
This study evaluated motivational interviewing (MI) in a permanent supportive housing agency. The agency’s contradictory social service and business missions resulted in an incompatible organizational culture theorized to diminish MI’s effectiveness. A combination of observational, interview, and archival data collected over 3 years were used to examine MI implementation within an incompatible supportive housing agency. Two major themes arose: how MI is used to categorize and change clients in permanent supportive housing and how worker–worker relationships affect MI implementation. The results suggest that within incompatible organizational environments, key elements of effective MI implementation are greatly weakened.